VARIASI PENGGUNAAN KATA SERAPAN BAHASA DAERAH DAN BAHASA ASING PADA NOVEL â€œRANAH 3 WARNAâ€ KARYA AHMAD FUADI - kurniati, lisdwiana; Tussolekha, Rohmah; Ridayani, Ridayani (Jurnal Bahtera: Jurnal Pendidikan, Bahasa, Sastra, dan Budaya, 2024)
Abstract : This research aims to describe the forms of use of variations in loanwords from regional and foreign languages through the process of adoption, adaptation and translation contained in the novel "Ranah 3 Warna" by Ahmad Fuadi. This research is a type of qualitative descriptive research. The results of the research show that there are 171 loan words from regional and foreign languages. There are 65 loanwords from regional languages, namely: 1) 2 words (1%) were found in the adoption form of adoption, 1 word was found in the Minang language (West Sumatra), and 1 word was found in Javanese, 2) 18 words were found in the adaptation form (9). %) from the Minang language (West Sumatra), 3) The translator's absorption form found 45 words (22.5%) from Minang language (West Sumatra) 38 words, Javanese 1 word, and Sundanese 6 words. For loanwords from foreign languages, there are 106, namely: 1) 11 words (5.5%) of adopted loan forms were found in English, 2 words in Arabic, 2 words in Dutch, and 1 word in Greek, 2) form Adapted absorption was found in 69 words (34.5%) from English 26 words, Arabic 17 words, Dutch 15 words, and Greek 11 words, 3) Translator's absorption form found 26 words (13%) from English 24 words , Arabic 1 word, and Greek 1 word. This research shows that the most frequently found absorption process is the adaptation process from a foreign language, namely English.